The Effect of Compensation and Work Motivation on Intention to Stay Through Job Satisfaction and Organizational Commitment to Employees - Ahmad Zaki Azzuhairi; Budi Eko Soetjipto; Puji Handayati (CV. AFDIFAL MAJU BERKAH, 2022)
This research is descriptive quantitative, and explanatory research. The independent variables of this study are the Compensation Variable (X1) and Work Motivation Variable (X2), and the Bound Variable is the Intention to Stay (Y). At the same time, the Mediation Variable is Job Satisfaction Variable (Z1) and Organizational Commitment Variable (Z2). The results of this study indicate that (1) Compensation variable has a positive and significant effect on Intention to Stay, (2) Work Motivation has a positive and significant effect on Intention to Stay, (3) Job Satisfaction has a positive and significant effect on Intention to Stay, (4 ) Organizational Commitment has a positive and significant effect on Intention to Stay, (5) Compensation variable has a positive and significant effect on Organizational Commitment, (6) Work Motivation has a positive and significant effect on Organizational Commitment, (7) Job Satisfaction has a positive and significant effect on Organizational Commitment , (8) Compensation variable has a positive and significant effect on Job Satisfaction, (9) Work Motivation has a positive and significant effect on Job Satisfaction, (10) Compensation Variable, (11) Work Motivation has a positive and significant effect on Intention to Stay through Organizational Commitment, (12) Job Satisfaction has a positive and significant effect on p Intention to Stay through Organizational Commitment, (13) Compensation variable has a positive and significant effect on Intention to Stay through Job Satisfaction, (14) Work Motivation has a positive and significant effect on Intention to Stay through Job Satisfaction.